2000
DOI: 10.1136/gut.46.5.597
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised study of intrasphincteric botulinum toxin in patients with oesophageal achalasia

Abstract: Background-Intrasphincteric injection of botulinum toxin (Botx) has been proposed as treatment for oesophageal achalasia. However, the predictors of response and optimal dose remain unclear. Aims-To compare the eVect of diVerent doses of Botx and to identify predictors of response. Patients/methods-A total of 118 achalasic patients were randomised to receive one of three doses of Botx in a single injection: 50 U (n=40), 100 U (n=38), and 200 U (n=40). Of those who received 100 U, responsive patients were reinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2
14

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(134 citation statements)
references
References 18 publications
6
112
2
14
Order By: Relevance
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…Achalasia and those who suffer from vigorous achalasia may benefit more from botulinum toxin [76] . A multicenter randomized study suggested that dose of botulinum toxin may be a predictor of outcome: the higher the dose, the better the response [77] . The use of botulinum toxin in achalasia was first introduced by Pasricha et al [78] .…”
Section: Botulinum Toxin Injectionmentioning
confidence: 99%
“…[3][4][5][6][7] An innovative endoscopic method for dissection of the LES, using a needle-knife to cut the muscular fibers from the lumenal side, was first described by Ortega et al 8 in 1980. Two decades later, Pasricha et al 9 first described the feasibility of an endoscopic submucosal esophageal myotomy in a survival animal model.…”
Section: Introductionmentioning
confidence: 99%